2006
DOI: 10.1088/0022-3727/39/8/022
|View full text |Cite
|
Sign up to set email alerts
|

Almost zero reflectance of a silicon oxynitride/porous silicon double layer antireflection coating for silicon photovoltaic cells

Abstract: Reflectance spectrum calculations for a silicon oxynitride (SiO x N y )-porous silicon (PS) double layer antireflection coating is performed using the matrix method. The results are compared with the corresponding spectrum of diamond-like carbon (DLC)/PS and SiO 2 /TiO 2 double layer coatings. A lower reflectance in the visible and infrared regions of the solar spectrum for the SiO x N y /PS double layer is obtained, especially in the 450-600 nm spectral range (with a flat reflectance response remaining as low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 14 publications
(23 reference statements)
0
26
0
Order By: Relevance
“…3 and 4, the calculated reflectance spectrum of nanoporous silicon dioxide (SiO 2 ) layer/SiO 2 /SiO x N y /PS (or other black silicon) multilayer ARC is broader than that of double-layer SiO x N y /PS ARCs, which has the best result as an ARC on the surface of silicon in all double layers ARC so far. 9 The reflectance of the double-layer SiO x N y /PS ARC at a low value for a spectral range from the wavelength of 420 nm to 800 nm, while the remaining part of the response is located well above reaching values up to 15% and at 350 nm wavelength.…”
Section: Resultsmentioning
confidence: 96%
“…3 and 4, the calculated reflectance spectrum of nanoporous silicon dioxide (SiO 2 ) layer/SiO 2 /SiO x N y /PS (or other black silicon) multilayer ARC is broader than that of double-layer SiO x N y /PS ARCs, which has the best result as an ARC on the surface of silicon in all double layers ARC so far. 9 The reflectance of the double-layer SiO x N y /PS ARC at a low value for a spectral range from the wavelength of 420 nm to 800 nm, while the remaining part of the response is located well above reaching values up to 15% and at 350 nm wavelength.…”
Section: Resultsmentioning
confidence: 96%
“…Bilayer AR SiO 2 coating on a silicon substrate can reduce the reflectance (<0.01%) in the visible region for solar cell applications [45] . However, the limitation of this coating restricts their usage at broader scale due to top porous, fragile nature of coating which has weak mechanical strength.…”
Section: Single Bilayer and Multilayer Ar Coatingsmentioning
confidence: 99%
“…Many studies have been reported for double layer antireflection (DLAR) coatings because single layer antireflection (SLAR) coatings are not able to cover a broad range of the solar spectrum [4][5][6][7][8]. Unfortunately, these multilayer antireflection coatings (ARCs) are expensive to fabricate owing to the stringent requirement of high vacuum, material selection, and layer thickness control.…”
Section: Introductionmentioning
confidence: 99%